Desintegración de la función motora en las enfermedades de Pick y Alzheimer Disintegration of motor functions in Pick's and Alzheimer's diseases - Alfredo F. Thomson (Arquivos de Neuro-Psiquiatria)
Symptoms of motor disintegration in presenile dementia (Pick's and Alzheimer's diseases) are presented. The paper is based in the study of 58 cases collected during a period of almost 24 years. Motor oral responses (sucking, rooting and pouting), motor rigidity (paratonic rigidity, pelvicrural flexion contraction), restless or quiescent positive motor responses (instinctive grasp reaction, grasp reflex) are related with frontal lesions. On the other hand, hypermetamorphosis and excessive oral tendency are believed to be in relation with temporal lobe lesions.